Disappointment: An essential factor among parents and children´s communication? - Yaranga Hernández, Mayra (2013)
This article intends to explain the worrying increase in the number of patricides occurring in Peru. By taking into consideration psychoanalytical theory and the concept of transitional object, as well as Craib’s pivotal work on the importance of disappointment, the article argues that criminal behaviour against parents may appear when the latter systematically allow their children to do or receive anything they want; this prevents them from experiencing the “disappointment” of not seeing all their wishes fulfilled. The role of self-esteem and parent- child communication is also discussed, and an example case is provided to illustrate the article’s main claim.